The Adenylyl Cyclase Inhibitor MDL-12,330A Potentiates Insulin Secretion via Blockade of Voltage-Dependent K+ Channels in Pancreatic Beta Cells - Li, Xiaodong; Guo, Qing; Gao, Jingying; Yang, Jing; Zhang, Wan; Liang, Yueqin; Wu, Dongmei; Liu, Yunfeng; Weng, Jianping; Li, Qingshan; Zhang, Yi (PLOS ONE, 2013)
Objective Adenylyl cyclases (ACs) play important role in regulating pancreatic beta cell growth, survival and secretion through the synthesis of cyclic AMP (cAMP). MDL-12,330A and SQ 22536 are two AC inhibitors used widely to establish the role of ACs. The goal of this study was to examine the effects of MDL-12,330A and SQ 22536 on insulin secretion and underlying mechanisms. Methods Patch-clamp recording, Ca2+ fluorescence imaging and radioimmunoassay were used to measure outward K+ currents, action potentials (APs), intracellular Ca2+ ([Ca2+]i) and insulin secretion from rat pancreatic beta cells. Results MDL-12,330A (10 µmol/l) potentiated insulin secretion to 1.7 times of control in the presence of 8.3 mmol/l glucose, while SQ 22536 did not show significant effect on insulin secretion. MDL-12,330A prolonged AP durations (APDs) by inhibiting voltage-dependent K+ (KV) channels, leading to an increase in [Ca2+]i levels. It appeared that these effects induced by MDL-12,330A did not result from AC inhibition, since SQ 22536 did not show such effects. Furthermore, inhibition of the downstream effectors of AC/cAMP signaling by PKA inhibitor H89 and Epac inhibitor ESI-09, did not affect KV channels and insulin secretion. Conclusion The putative AC inhibitor MDL-12,330A enhances [Ca2+]i and insulin secretion via inhibition of KV channels rather than AC antagonism in beta cells, suggesting that the non-specific effects is needed to be considered for the right interpretation of the experimental results using this agent in the analyses of the role of AC in cell function.